Teachers Are Not Oppressors - Ketler Sitohang; Grace Metaria Sihombing; Debora Sitohang; Binsar Simanjuntak; Hisardo Sitorus (FKIP, Universitas Palangka Raya, 2024)
Teachers must create a safe, comfortable and positive environment during learning so that students experience a pleasant process so that they focus on learning. Students should not be stressed when taking lessons because it will make students not want to be creative. Teachers are often seen as authoritarian figures who can intimidate students, as oppressors who only want to impose their will without considering students' needs. The method used in this research is a qualitative method through literature study sourced from various journal articles, books and other references to facilitate understanding of the objects discussed. The focus of this research is whether teachers are bullies or teachers who are not bullies. Teachers have good character or good personality competence, respect other people, have a passion for teaching, nurturing, encouraging and motivating, and create a safe and positive learning environment to produce students who are useful to many people. Teachers are not oppressors. Teachers are not people who force or pressure students, but rather educators who are wise, encouraging, and a source of comfort and support for students' positive development. Interactions between teachers and students should be based on respect, understanding and good communication. So the profession shown by a teacher is that teachers are not oppressors.